Data analytics the ultimate guide to big data analytics for business, data mining techniques, data collection, and business intelligence concepts - Jones, Herbert ([publisher not identified], 2018)
With this book, not only the reader understand all the internal nitty-gritties about data analytics and data mining,but they will also understand why data analytics and data mining is changing the business arena. They will realized that the high-performance analytics will enable them to do stuff that them never thought about before probably because the volumes of data were just too big (among other reasons) and so much more.